Are founding families special blockholders? An investigation of controlling shareholder influence on firm performance - Isakov, Dušan; Weisskopf, Jean-Philippe (Journal of Banking & Finance, 2014)
This paper examines how family and non-family ownership affects the performance of Swiss listed firms from 2003 to 2010. We distinguish between these two types of controlling shareholders since they have different objectives. We hypothesise that only family shareholders have a real incentive to reduce agency costs whereas non-family blockholders are similar to widely held companies. Our results show that family firms are more profitable than companies that are widely held or have a non-family blockholder. For market valuations we find that the family stake plays a critical role and document a concave relationship between family ownership and Tobin’s Q. We also investigate the impact of different features of family firms on performance, and document that the generation of the family and the active involvement of the family play an important role for market valuation.